Strength of Flanged and Plain Cruciform Members - Nicholas Harris; Girum Urgessa (Advances in Civil Engineering)
There are two different types of cruciform members used in practice. Flanged cruciform sections are typically fabricated from two hot-rolled WT sections welded to the web of a standard hot-rolled I section, whereas plain cruciform sections are typically fabricated from two symmetric rectangular plates welded in the form of a cross. Cruciform members that are subjected to combined compression and bending are typically limited by torsional buckling unlike conventional compression members (such as W-shapes) that are typically limited by flexural (Euler) buckling about their local weak axis of bending. Detailed guidance on the analysis of flanged and plain cruciform members is scarce in literature. Hence, this paper presents numerical studies on the strength capacities of both flanged and plain cruciform members that are subjected to combined compression and bending effects. Analysis results show the ability of flanged and plain cruciform to resist lateral-torsional buckling over longer unbraced lengths, allowing development of efficient plastic resistance.